Entre campagne publicitaire et films d’auteur : douze paysages urbains italiens au cinéma - Olivier Gaudin (Projets de Paysage)
12 Registi per 12 città (1989) is a commissioned promotional film comprising twelve portraits of cities, produced by twelve famous Italian filmmakers before the 14th World Cup (Italia’90). It is an exemplary body of works which can be used to study the relationship between the representation of the urban landscape and the advertising image. How are cities represented in these films? What do these portrayals, which follow a logic based on the market, tourism and the heritage, demonstrate? The article examines the respective roles given in these films to landscapes, aerial views, historical monuments, and specific elements within the sites (relief, water); it also takes a look at variations in the attention focused by the filmmakers on the public places, the sonic environments, the inhabitants and the day-to-day activities in these cities. These technically sophisticated commercial films are the result of aesthetic choices that sometimes distinguish them from the spectacular and commercial rationale of mass tourism which they nevertheless are a part of. Analysing them makes it possible to fully appreciate the production of urban images and the tourist experience.